Diseño de un plan de intervención en factores de riesgo psicosocial para una empresa de construcción (2013)
This degree work was conducted in the company INFERCAL S.A., started with measuring the psychosocial risk factors, counted with the participation of 20 workers using the battery of instruments developed by the Javeriana University and the Ministry of Social Protection. The following data questionnaires were applied: questionnaire of labor interior factor A and B sheet, of outside labor factors and questionnaire for the evaluation of stress questionnaire. The questionnaires with the application designed by the same entities were tabulated, and from the analysis of results, was designed a plan of intervention in psychosocial risk factors aimed at leaders and employees of the company, which aims to have an impact, reducing the risk level of this stress and psychosocial.